Rehearsing post‐Covid‐19 citizenship: Social representations of UK Covid‐19 mutual aid. (29th March 2022) - O'Dwyer, Emma; Souza, Luiz Gustavo Silva; Beascoechea‐Seguí, Neus
Abstract: People across the world have responded to the pandemic by mobilizing and organizing to support their communities, setting up mutual aid groups to provide practical, financial, and social support. Mutual aid means short‐term 'crisis response' for some, while for other groups, it is a chance to radically restructure society, and what it means to be a member of that society. Drawing on social representations theory and previous work on citizenship in social and political psychology, we examined the ways in which mutual aid was understood and performed by members of UK Covid‐19 mutual aid groups. We conducted 29 interviews with members of these groups in May/June 2020. A reflexive thematic analysis showed that mutual aid groups were characterized as complex, efficient, and non‐hierarchical units, operating on the principles of solidarity, kindness, and trust. Two tensions were evident in the data, specifically between (1) collaboration with existing organizations and structures (e.g., local government and the police), and resistance to it and (2) maximizing group inclusivity and sustaining political critique. Findings are discussed in relation to existing theoretical and empirical work on citizenship and mutual aid groups.